miRNAs in decidual NK cells: regulators worthy of attention during pregnancy - Liman Li; Ting Feng; Weijie Zhou; Yuan Liu; Hong Li (BMC, 2021)
Abstract The critical immune effectors, including T, B, and natural killer (NK) cells, dendritic cells, and macrophages participate in regulating immune responses during pregnancy. Among these immune cells, decidual NK (dNK) cells are involved in key placental development processes at the maternal-fetal interface, such as uterine spiral artery remodeling, trophoblast invasion, and decidualization. Mechanistically, dNK cells significantly influence pregnancy outcome by secreting cytokines, chemokines, and angiogenic mediators and by their interactions with trophoblasts and other decidual cells. MicroRNAs (miRNAs) are small non-coding RNA molecules that participate in the initiation and progression of human diseases. Although the functions of circulating miRNAs in pathological mechanism has been extensively studied, the regulatory roles of miRNAs in NK cells, especially in dNK cells, have been rarely reported. In this review, we analyze the effects of miRNA regulations of dNK cell functions on the immune system during gestation. We discuss aberrant expressions of certain miRNAs in dNK cells that may lead to pathological consequences, such as recurrent pregnancy loss (RPL). Interestingly, miRNA expression patterns are also different between dNK cells and peripheral NK (pNK) cells, and pNK cells in the first- and third‐trimester of gestation. The dysregulation of miRNA plays a pivotal regulatory role in driving immune functions of dNK and pNK cells. Further understanding of the molecular mechanisms of miRNAs in dNK cells may provide new insights into the development of therapeutics to prevent pregnancy failure.